Chinese and Indian interpretations of pain: A qualitative evidence synthesis to facilitate chronic pain management - Lewis GN; Shaikh N; Wang G; Chaudhary S; Bean D; Terry G (John Wiley and Sons, Inc., 2023)
Objective People from minority ethnicities often have a greater impact of chronic pain, are underrepresented at pain services, and may not benefit from treatment to the same extent as dominant cultures. The aim of this study was to review Indian and Chinese cultural views of pain and pain management, as a basis for improving management of chronic pain in migrant populations from these ethnicities. Methods A systematic review of qualitative studies addressing pain beliefs and experiences involving Indian and Chinese participants was conducted. Thematic synthesis was used to identify themes across the studies, and the quality of the articles was appraised. Results Twenty-six articles were included, most of which were appraised as high quality. Five themes were identified: Making meaning of pain described the holistic interpretation of the meaning of pain; Pain is disabling and distressing described the marked physical, psychological, and spiritual impact of pain; Pain should be endured described the cultural expectation to suppress responses to pain and not be a burden; Pain brings strength and spiritual growth described the enrichment and empowerment some people experienced through living with pain, and Management of pain goes beyond a traditional or Western approach described the factors that guided people in their use of healthcare. Discussion The review identified a holistic interpretation and impact of pain in Indian and Chinese populations, with pain management guided by multiple factors that transcended a single cultural framework. Several strength-based management strategies are recommended based on preferences for traditional treatments and respect for Western healthcare.
Keywords: culture; ethnicity; interpretation; pain; qualitative synthesis